2018
DOI: 10.1111/jvh.12912
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis B virus infection in Taiwan: The role of NTCP rs2296651 variant in relation to sex

Abstract: Sodium taurocholate cotransporting polypeptide (NTCP) is a functional receptor for hepatitis B virus (HBV) infection. NTCP rs2296651 is believed to be an Asian-specific variant responsible for HBV susceptibility. We investigated the relationship between rs2296651 and HBV infection in Taiwan based on stratification by gender and menopausal status. We recruited 10 017 Taiwan Biobank participants aged 30-70 years with complete genetic data and sociodemographic information. Gender-stratified multivariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
9
2
Order By: Relevance
“…The NTCP p.Ser267Phe mutation cannot completely block HBV infection in vivo for 8.57% (15/175) of p.Ser267Phe mutation homozygotes were reported to be HBV-infected. In detail, 6 of 32 homozygotes in our cohort, 5 of 42 homozygotes in Hu's study (Hu et al, 2016), 2 of 2 homozygotes in Wang's study (Wang et al, 2017), 1 of 2 homozygotes in An's study (An et al, 2018), 1 of 12 homozygotes in Zhang's study (Zhang et al, 2017), and 0 of 85 homozygotes in Nfor's study (Nfor et al, 2018) were reported to be HBV infection. The HBV-infected p.Ser267Phe mutation homozygotes all had low or negative viral loads.…”
Section: Discussionmentioning
confidence: 58%
“…The NTCP p.Ser267Phe mutation cannot completely block HBV infection in vivo for 8.57% (15/175) of p.Ser267Phe mutation homozygotes were reported to be HBV-infected. In detail, 6 of 32 homozygotes in our cohort, 5 of 42 homozygotes in Hu's study (Hu et al, 2016), 2 of 2 homozygotes in Wang's study (Wang et al, 2017), 1 of 2 homozygotes in An's study (An et al, 2018), 1 of 12 homozygotes in Zhang's study (Zhang et al, 2017), and 0 of 85 homozygotes in Nfor's study (Nfor et al, 2018) were reported to be HBV infection. The HBV-infected p.Ser267Phe mutation homozygotes all had low or negative viral loads.…”
Section: Discussionmentioning
confidence: 58%
“…Several studies have indicated that variants of rs2296651 either increases an individual's susceptibility to HBV infection and/or its complications, makes resolution/viral clearance of the infection faster or improves the prognostic outcome of cirrhosis and HCC [15,[19][20][21][22]. The evidence of the transferability of rs2296651 associated with HBV infection has been demonstrated among the Han population [15], Taiwanese [24] and Vietnamese [19]. The study has some limitations that should be acknowledged.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have reported the presence of SLC10A1 rs2296651, rs61745930, and rs4646287 SNP variants among persons with HBV infection (4,14,24). Thus, we determined the association between 3 SNPs in the SLC10A1 gene (rs2296651, rs61745930, and rs4646287) and the risk of HBV infection among the Ghanaian population.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that variants of rs2296651 either increases an individual's susceptibility to HBV infection and/or its complications, makes resolution/viral clearance of the infection faster or improves the prognostic outcome of cirrhosis and HCC [15,[19][20][21][22]. The evidence of the transferability of rs2296651 associated with HBV infection has been demonstrated among the Han population [15], Taiwanese [24] and Vietnamese [19]. However, unlike our results, rs2296651 [(c.800C > T) (S267F)] has been associated with reduced HBV infection and associated hepatic complications [25].…”
Section: Discussionmentioning
confidence: 99%